Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure - Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Ehret, Georg B; Amin, Najaf; Mooser, Vincent; Dörr, Marcus; Esko, Tõnu; Pirastu, Nicola; Pichler, Irene; et al. (Nature genetics, 2011)
Paul Elliott, Martin Tobin, Cornelia van Duijn and colleagues report a genome-wide association study for pulse pressure and mean arterial pressure, identifying six new loci influencing these two traits. Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans 1 , 2 , 3 . We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery ( N = 74,064) and follow-up studies ( N = 48,607), we identified at genome-wide significance ( P = 2.7 × 10 −8 to P = 2.3 × 10 −13 ) four new PP loci (at 4q12 near CHIC2 , 7q22.3 near PIK3CG , 8q24.12 in NOV and 11q24.3 near ADAMTS8 ), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1 ) and one locus associated with both of these traits (2q24.3 near FIGN ) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.